Fractal model of transdermal drug delivery - Walicka, Anna; Iwanowska-Chomiak, Beata (Zielona Góra: Uniwersytet Zielonogórski)
Skin, separating the vital organs of a human body, is a desirable route for drug delivery. However, the intact skin is normally permeable only for drug molecules with a low molecular weight. The stratum corneum (SC), being the outermost layer of the skin and the epidermis being the second - more permeable - layer of the skin, play an essential function in transdermal drug delivery. Physical and chemical methods of skin poration are used to enhance transdermal drug delivery.
Keywords: drug delivery; human skin; epidermis; fractal models